(untitled) (Contemporary Mathematics, 2025)
An exploration of various human capital trends and skill requirements of human resource (HR) professionals strengthen the argument to build the talent pool that can utilize analytics for making the right HR decisions. In this context, the present study identified the analytical competencies required for HR professionals and prioritized them. Based on the literature in the area of HR analytics and analytical competencies, a 20-item survey instrument was developed and served to HR professionals. Responses from 390 HR professionals were collected, and data analysis was performed using descriptive and multivariate statistical techniques such ast-test and analysis of variance (ANOVA). The trapezoidal fuzzy approach, a Multi-Criteria Decision-Making method, has been used in the present study to prioritize and rank the analytical competencies. The results of the study indicate that there were no differences in analytical competencies by age and total work experience of HR professionals. HR professionals were having a reasonably good amount of understanding of several analytical competencies yet required further advancement to explore HR analytics fully. The present research contributes to analyzing various trends in changing skill requirements of HR professionals in light of the emergence of HR analytics, an area not widely studied from the viewpoint of HR professionals’ readiness. Using the results, organizations can focus on the right skills in which professionals need training. Analytical competencies have been examined in the context of HR analytics for the first time using an multi-criteria decision-making (MCDM) approach. The research is novel in prioritizing analytical competencies using a trapezoidal fuzzy approach.